IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) BERDASARKAN KONSEP TRIPLE BOTTOM LINE - Juliano, Kelvin Allen; Rofiaty, Rofiaty (Jurnal Kewirausahaan dan Inovasi, 2023)
The objective of this research is to identify the implementation of Corporate Social Responsibility (CSR) program by the Regional Office of PT Bank Rakyat Indonesia (Persero) Tbk in Malang. The program was implemented using the Triple Bottom Line concept known as the 3Ps, consisting of profit, people, and planet, in order to create corporate image. The data of this qualitative descriptive research was harvested from documentation and interviews with the office’s logistics staff as the executor of the program. This study finds that the Regional Office of PT Bank Rakyat Indonesia has carried out its Corporate Social Responsibility program well and harmoniously based on the Triple Bottom Line. Past studies have found that there are components of the program which were not optimally implemented and irrelevant to be applied this year. Therefore, this research suggests the office (a) to supervise its CSR activities, (b) to conduct controlling to ensure the accuracy of the program, (c) to maintain the consistency of its CSR implementation, and (d) to take advantage from the positive impacts for the company’s sustainability and the attainment of Good Corporate Governance (GCG).